2011
DOI: 10.1002/bmc.1677
|View full text |Cite
|
Sign up to set email alerts
|

Salivary peptidome in type 1 diabetes mellitus

Abstract: Diabetic patients show a high susceptibility to oral diseases of inflammatory, catabolic and chronic nature with potential impact on saliva composition. In this study, our purpose was to characterize type 1 diabetes-induced alterations in the salivary peptidome aiming to find prospective biomarkers for type 1 diabetes oral health evaluation. Peptidomic analysis of saliva from controls (n = 5) and type 1 diabetic patients (n = 5) were performed by liquid chromatography followed by mass spectrometry. The proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
1
19
0
2
Order By: Relevance
“…After 18 h and 115 h of incubation, the majority of the eluted peptides belonged almost exclusively to the different PRP isoforms, suggesting that these proteins display the highest susceptibility to ex vivo proteolysis. Cleavage site analysis showed that the peptide bond between GlnGly residues was the preferential site for proteolysis, which is in agreement with previous findings [29][30][31][32]. Interestingly, the formation of the new PRPs peptides is associated with a time-dependent profile of proteases, a variation never reported so far, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After 18 h and 115 h of incubation, the majority of the eluted peptides belonged almost exclusively to the different PRP isoforms, suggesting that these proteins display the highest susceptibility to ex vivo proteolysis. Cleavage site analysis showed that the peptide bond between GlnGly residues was the preferential site for proteolysis, which is in agreement with previous findings [29][30][31][32]. Interestingly, the formation of the new PRPs peptides is associated with a time-dependent profile of proteases, a variation never reported so far, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Despite inter-individual variability, PRPs, P-B peptide, histatin 1 and 3, mucin 7, polymeric immunoglobulin receptor and statherin represented the most susceptible salivary proteins to proteolysis in vivo, as proven by the number of peptides identified to these proteins at T0 (Table 1) which is corroborated by the LC-MS/MSbased characterization of whole salivary peptidome [29][30][31]. Protein fragments at T0 were attributed to the activity of CTSL1 and MEP1A.…”
Section: Discussionmentioning
confidence: 65%
“…These proteins may be involved in the development of DM associated complications or are markers for such complications ( 56 ). Another study on Type 1 DM induced salivary peptidome alterations revealed high activity of proteases such as matrix metalloproteinase-9 (MMP-9) and cathepsin D and presented salivary collagen fragments as potential biomarkers to follow up DM-related oral damage ( 57 ). Salivary proteomic profiles in patients with periodontitis and healthy subjects, showed distinct change in proteins in presence of inflammation, which can lead to the improvement of periodontal disease diagnosis ( 58 ).…”
Section: Saliva As a Fluid For Omics Studymentioning
confidence: 99%
“…Proteomic techniques such as two-dimensional electrophoresis (2-DE), 2D-liquid chromatography/mass spectrometry (2D-LC/MS), matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF/MS), and surface enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF/MS), have been used in saliva studies. Based on those techniques, potential salivary biomarkers for diseases such as Sjögren syndrome [20], diabetes mellitus [21] and some different cancers [22] have been suggested. 2-DE has been one technique of choice for the global analysis and initial profiling of salivary proteins, being used as a first step for protein separation, followed by MS or tandem MS (MS/MS) [23].…”
Section: Introductionmentioning
confidence: 99%